RELEVANSI KURIKULUM 2013 DENGAN PEMBELAJARAN PAI DALAM UPAYA PEMBENTUKAN KARAKTER PESERTA DIDIK - Abdullah K; Fahmiah Akilah (Adaara: Jurnal Manajemen Pendidikan Islam, 2020)
Conceptually, the 2013 curriculum relied heavily on Scientific methods, which in its application were more popular with the term 5 M: Mengamati (observing),Menanya(asking), Mengumpul (gathering), Menalar (reasoning) and Mengkomunikasikan (communicating), and applied through scientific methods and approaches, such as: Contextual Teaching Learning, Enquiry, Problem Solving, Communicative, Cooperative and so on.And always starting and guided by the core curriculum, which is known by the four Main Competences (KompetensiInti/KI), namely: KI. 1: Spiritual Attitude KI.2: Social Attitude, KI. 3: Knowledge, and KI.4: Skills. The cultivation of character is integrated with the learning of Islamic Religious Education, so that the implementation is in line and agreed in shaping the mental attitude, social attitude, knowledge and skills.This means that humans who will be formed are people mentality or morality, intellectual andskills, or who will be formed is the heart (affective aspects), mind (cognitive aspects) and hands or feet (psycho-psychological aspects). In order for the students to have good moralsand avoid being chipped (mazmumah morals).The building up of the character values refers to the 2013 curriculum established by Ministry of National Education No. 68 of 2013 for Junior High School (SMP / MTs), namely: Faith, honesty, discipline, responsibility, care, (tolerance, mutual cooperation), polite, confidence in interacting effectively with the social and natural environment in the social term.The character has been instilled by Islamic Education (PAI) teachers who are quite professional, so that the results are quite intense, high, positive and entrenched, because the aim is the same, namely: forming commendable morals and avoiding despicable morals.